MINIMUM COVERING SEIDEL ENERGY OF A GRAPH - Rajesh Kanna; Jagadeesh R; Mohammad Reza Farahani (Journal of the Indonesian Mathematical Society, 2016)
In this paper we have computed minimum covering Seidel energies ofa star graph, complete graph, crown graph, complete bipartite graph and cocktailparty graphs. Upper and lower bounds for minimum covering Seidel energies of agraphs are also established.DOI : http://dx.doi.org/10.22342/jims.22.1.234.71-82